High-resolution forest carbon mapping for climate mitigation baselines over the RGGI region, USA. (23rd February 2021) - Tang, Hao; Ma, Lei; Lister, Andrew; O'Neill-Dunne, Jarlath; Lu, Jiaming; Lamb, Rachel L; Dubayah, Ralph; Hurtt, George
Abstract: Large-scale airborne lidar data collections can be used to generate high-resolution forest aboveground biomass maps at the state level and beyond as demonstrated in early phases of NASA's Carbon Monitoring System program. While products like aboveground biomass maps derived from these leaf-off lidar datasets each can meet state- or substate-level measurement requirements individually, combining them over multiple jurisdictions does not guarantee the consistency required in forest carbon planning, trading and reporting schemes. In this study, we refine a multi-state level forest carbon monitoring framework that addresses these spatial inconsistencies caused by variability in data quality and modeling techniques. This work is built upon our long term efforts to link airborne lidar, National Agricultural Imagery Program imagery and USDA Forest Service Forest Inventory and Analysis plot measurements for high-resolution forest aboveground biomass mapping. Compared with machine learning algorithms ( r 2 = 0.38, bias = −2.3, RMSE = 45.2 Mg ha −1 ), the use of a linear model is not only able to maintain a good prediction accuracy of aboveground biomass density ( r 2 = 0.32, bias = 4.0, RMSE = 49.4 Mg ha −1 ) but largely mitigates problems related to variability in data quality. Our latest effort has led to the generation of a consistent 30 m pixel forest aboveground carbon map covering 11 states in the Regional Greenhouse Gas Initiative region of the USA. Such an approach can directly contribute to the formation of a cohesive forest carbon accounting system at national and even international levels, especially via future integrations with NASA's spaceborne lidar missions.